Minocycline alleviated scopolamine-induced amnesia by regulating antioxidant and cholinergic function. Issue 2 (February 2023) - Eshaghi Ghalibaf, Mohammad Hosein; Rajabian, Arezoo; Parviz, Mohsen; Akbarian, Mahsan; Amirahmadi, Sabiheh; Vafaee, Farzaneh; Hosseini, Mahmoud
Abstract: Background and aim: Minocycline, a tetracycline derivative, has been found to exert neuroprotective properties. The current project aimed to assess the antioxidant status and cholinergic function in the amnesia induced by scopolamine. Methods: We evaluated the passive avoidance performance, acetylcholine esterase (AChE) enzyme activity, and the oxidative stress indicators in the following groups: Normal control, scopolamine, and the treatment groups (the animals were given minocycline (10–30 mg/kg)). Results: Scopolamine (intraperitoneal) injection was associated with impairment of passive avoidance performance and neurotoxicity. Minocycline pronouncedly ameliorated scopolamine injury as presented by the increased latency time to darkness and stay time in lightness along with the decreased darkness entry. Moreover, minocycline decreased lipid peroxidation, while it elevated the levels of superoxide dismutase, AChE enzymes, and thiol groups in both the cortex and hippocampus. Conclusion: Our data suggested that minocycline modulated the antioxidant status and AChE in the brains, which may contribute to its protective effects against scopolamine-induced amnesia.